Tuesday

March 31, 2015

March 31, 2015

Posted by **Linda** on Monday, November 14, 2011 at 4:32pm.

3x – 15y = -12

3x + 24y = -12

- algebra -
**Reiny**, Monday, November 14, 2011 at 6:46pmRather than substitution, why don't we just subtract them as they stand.

-29y = 0

y = 0

then 3x = -12

x = -4

If you really have to use substitution,

form the first , 3x = 15y - 12

into the 2nd

15y - 12 + 24y = -12

29y = 0

then 3x = 15(0) - 12

3x = -12

x = -4

**Answer this Question**

**Related Questions**

Algebra - using the substitution method. Show your work. If the system has no ...

math - use the substitution method. Show your work. If the system has no ...

intermediate algebra - Solve uing the subtitution method. Show your work. If the...

algebra - Solve using the substitution method. Show your work. If the system has...

Algebra - Solve using the substitution method. Show your work. If the system has...

Algebra - Solve using the substitution method. Show your work. If the system has...

Algebra - Solve using the substitution method. Show your work. If the system has...

algebra - Solve using the substitution method. Show your work. If the system has...

Algebra - Solve using the substitution method. Show your work. If the system has...

algebra - Solve using the substitution method. Show your work. If the system has...